Cyber Crimes and Extradition Issues in India: Towards a Multilateral Approach in Combating Cybercrimes (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The incredible evolution of information society and its dependence on Internet usage in world and particularly in India is laterally accompanied by vulnerability of societies to cybercrime. Cybercriminals are not constrained by geographical limitations as cyberspace is a free-flowing, borderless and a global problem. These crimes can't be deterred by local laws, India in such scenario is like sitting ducks. India to counter Cybercrime has engaged itself in various bilateral agreements like cyber agreement with Russia and a framework agreement with the US, resent visit of prime minister of India Mr. Modi to Israel to sign Indo-Israel cyber framework is yet another effort of India to streamline its cyberspace. These bilateral agreements have limited scope and are inadequate and ineffective to deal with cybercrime. India need a multilateral treaty which will harmonize its laws by a common criminal policy, and deal with international cooperation for combating cybercrimes at global level. The treaty should help in formulating effective legislation and robust investigative techniques, which can foster international cooperation to combat cybercrime. The Council of Europe's Budapest Convention on Cybercrime is such international multilateral treaty dealing with international cooperation for combating cybercrimes at global level. India should sign the convention to combat cybercrime, even the US and Israel with whom India is having bilateral agreements to combat cybercrime have joined Budapest cybercrime convention.